Ortega, Camba y sus circunstancias - Hernández Les, Juan A. (Estudios sobre el Mensaje Periodístico, 2007)
The study of the figure of José Ortega y Gasset like journalist has an enormous importance in the study of the Spanish journalism. Ortega dedicated great part of his life to write for the journals and the magazines. Many of his articles shaped his books and later essays. The parallelism with Julio Camba is extraordinary because as Camba also wrote for the newspapers and, finally, many of his articles transformed in literary units with own unmistakable style. This article analyzes the journalism of Camba and Ortega in relation to a certain epoch, the Spanish Republic, and confront the problem of the singularity that supposes doing journalism without losing the condition of intellectual and writer.